2017
DOI: 10.1002/jcph.1008
|View full text |Cite
|
Sign up to set email alerts
|

Repeated‐Dose Oral N‐Acetylcysteine in Parkinson's Disease: Pharmacokinetics and Effect on Brain Glutathione and Oxidative Stress

Abstract: Parkinson's disease (PD) is associated with oxidative stress and decreased nigral glutathione (GSH), suggesting that therapies that boost GSH may have a disease-modifying effect. Intravenous administration of a high dose of N-acetylcysteine (NAC), a well-known antioxidant and GSH precursor, increases blood and brain GSH in individuals with PD and with Gaucher disease and in healthy controls. To characterize the pharmacokinetics of repeated high oral doses of NAC and their effect on brain and blood oxidative st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
73
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 120 publications
(88 citation statements)
references
References 43 publications
1
73
0
1
Order By: Relevance
“…A number of treatments have been directed at this finding, including peripheral GSH infusions (not proven to cross the blood–brain barrier). In a recent study, supplementation with N‐acetylcysteine, a GSH precursor, significantly increased peripheral antioxidant measures (catalase and GSH/Glutathione disulfide (GSSG)), but failed to increase brain GSH (using proton magnetic resonance spectroscopy at 3 and 7 tesla), possibly related to low oral N‐acetylcysteine (NAC) bioavailability . EPI‐589 (also known as [R]‐troloxamide quinone in amyotrophic lateral sclerosis research), a drug claimed to catalytically increase GSH in cells, is being evaluated in a phase 2a safety and biomarker study in mitochondrial genetic subtypes as well as sporadic PD (NCT02462603).…”
Section: Targets For Disease Modificationmentioning
confidence: 99%
“…A number of treatments have been directed at this finding, including peripheral GSH infusions (not proven to cross the blood–brain barrier). In a recent study, supplementation with N‐acetylcysteine, a GSH precursor, significantly increased peripheral antioxidant measures (catalase and GSH/Glutathione disulfide (GSSG)), but failed to increase brain GSH (using proton magnetic resonance spectroscopy at 3 and 7 tesla), possibly related to low oral N‐acetylcysteine (NAC) bioavailability . EPI‐589 (also known as [R]‐troloxamide quinone in amyotrophic lateral sclerosis research), a drug claimed to catalytically increase GSH in cells, is being evaluated in a phase 2a safety and biomarker study in mitochondrial genetic subtypes as well as sporadic PD (NCT02462603).…”
Section: Targets For Disease Modificationmentioning
confidence: 99%
“…NAC with oral supplementation between infusions. One study using only oral NAC (6,000 mg/day) revealed no increase in glutathione levels in the brain as measured by MRS, whereas the same group showed an increase in brain glutathione levels in a study of patients with PD receiving i.v. NAC .…”
Section: Discussionmentioning
confidence: 99%
“…NAC . An early pharmacokinetic study showed that oral NAC resulted in about 1/10 of the amount of NAC in the serum compared with being given i.v., and increasing the oral dose substantially may not lead to higher serum concentrations …”
Section: Discussionmentioning
confidence: 99%
“…Our interest in GSH led to additional 1 H-MRS work, where we utilized 8 mL occipital ROIs to measure GSH concentrations in two pharmacodynamic studies of the GSH precursor N-acetylcysteine (NAC): (1) a single (i.v.) dose study; and (2) a repeated oral dose trial [116,117]. The i.v.…”
Section: Neurochemical and Metabolic Imagingmentioning
confidence: 99%
“…Our 4 week daily oral NAC dose study in PD and control subjects showed blood antioxidant parameter increases (though 10-fold lower than the increases seen in the i.v. study), and trends, but not statistically significant, brain GSH increases [117]. The goal of the oral NAC study was to help determine dosing for a longer oral NAC clinical trial planned by colleagues at the University of California at San Francisco.…”
Section: Neurochemical and Metabolic Imagingmentioning
confidence: 99%